The predictive effects of students’ perception of teaching practices in TV instruction on students’ self-efficacy - Plazinić, Ljiljana (Psihološka istraživanja, 2021)
The COVID-19 pandemic forced school closures worldwide. TV instruction became one of the main distance-learning modalities across the globe. Given the scarce evidence of effects of TV instruction on students and broad evidence that quality of teaching is a vital factor of students’ achievements and motivational beliefs, the main objective of this study is to examine the relationship between the perceived quality of TV teaching practices and one of the most important student outcomes – academic self-efficacy. Sample consisted 1904 primary and lower secondary students. We constructed two measures of self-efficacy: a general measure of student’s self-efficacy with regard to the subject and a situational measure of self-efficacy towards the current TV lesson. Students’ perception of teaching practices was measured by a composite scale made of ten statements. We conducted regression and mediation analysis in order to identify potential mediation of general self-efficacy in the given subject. Students’ perception of teaching practices was found to be a significant predictor that explained 40.55% of the variance of situational self-efficacy towards the current lesson, and the 14% of total effect was mediated by general students’ self-efficacy. The results indicate that, even in the indirect and asynchronous TV instruction, teachers can nurture student self-efficacy towards current lessons and tasks by creating a supportive environment, providing clear representation of knowledge, emphasizing the relevance of the learning content by linking the new material and concepts to the students’ life experiences and prior knowledge, and by giving challenging tasks to enhance students’ engagement.